Implicit Textually Enhanced Processing of Aspectual Meanings in English Learners with German as a First Language. Issue 7 (9th August 2022) - Schramm, Andreas; Haser, Verena; Mensink, Michael C.; Reifenrath, Jonas; Kassemi, Parinaz
ABSTRACT: This research addresses implicit learning of temporal meanings in English by adult non-native readers of German, a language without morphosyntactic imperfective aspect. Twenty-four learners from mixed first languages participated in a norming study assessing unenhanced aspect awareness. Then, in a second experiment, 91 native-German learners participated in quantitative (word completion; question-answering; truth value judgment) and, in a third experiment, a subset of seven in qualitative measures (stimulated recall, interview). We build on previous theorizing that assumes initially advanced understanding of perfective compared to imperfective aspect, the use of the latter having to be learned in our new narrative context, and later acquisition stages to exhibit implicit rather than explicit knowledge. We expect that second-language learners profit from awareness created through textually enhanced materials, which leads to fairly implicit learning and thus to improvement in understanding of and knowledge about imperfective aspect. We investigated the learning of aspect in pragmatic (story) and semantic (sentence) contexts. Semantically, aspect specifies whether an event is ongoing or completed; pragmatically, whether it subsequently aids causal inferencing or not. Our data partly confirm our expectations, showing initial awareness of perfective aspect (semantic and pragmatic context) and gradually improved understanding (pragmatic and eventually even semantic context) as well as rapidly improved explicit knowledge of imperfective aspect, which in turn appears to trigger implicit perfective-aspect knowledge. These findings and separate trajectories advance our understanding of language learning and support the call for implicit learning techniques in second-language teaching and learning.